Ultrasonic dispersion of micro crystalline cellulose for developing cementitious composites with excellent strength and stiffness - Parveen, Shama (2018)
This paper reports the first attempt to utilize ultrasonication energy for homogeneously dispersing microcrystalline cellulose (MCC) to develop MCC reinforced cementitious composites. Aqueous suspensions of MCC (1.0–5.0 wt.% with respect to water) were prepared using ultrasonication treatment and the suspensions were then added to the cement mortar mixes. The aqueous suspensions were characterized using optical microscopy for the area of MCC agglomerates and using UV–Vis spectroscopy for the concentration of well dispersed MCC and extractability and accordingly, the ultrasonication time was optimized. The developed cementitious composites, after 28 days of hydration, were characterized for their flexural and compressive properties. Selected samples were also analyzed for fracture surface, porosity and degree of cement hydration. Experimental results suggested that an ultrasonic treatment of 30 min could ensure good MCC dispersion with low agglomerated areas and high extractability. Flexural modulus, flexural strength and compressive strength improved strongly with MCC addition, leading to maximum improvements of 96%, 19.2%, and 51.4% using only 1 wt.% MCC. Moreover, addition of MCC to cementitious composites resulted in improved cement hydration and reduction in pore size of cementitious composites.